Influence Of Human Resource Practices, Job Satisfaction And Person-Organization Fit On Job Performance Of Private Healthcare Employee In Jordan’s Medical Tourism Industry. - Amarneh, Saleh Omar Saleh (2020)
This study outlines and tests a wide range model of human resource management (HRM) practices and its association with outcomes through a path including employee attitudes and behaviours. In view of this, this study will provide a mechanism to support the role played by private hospitals employees to improve the medical tourism industry in Jordan. Drawing on social exchange theory, this study contributes a new way of opening the so-called ‘black box’ between HRM practices and performance. Furthermore, this study aims to assess the moderating effect of person-organization (P-O) fit in the relationships of recruitment and selection, job design, training and development, employee empowerment, performance appraisal, compensation and job satisfaction. This mechanism contributes to enhance the knowledge on the relationship between HRM and P-O fit by examining possible moderating roles of P-O fit in the relationship between HRM practices and employee job satisfaction. The study focuses on two self-report measures called employee job performance: organizational citizenship behaviour and task performance. Data were collected via non-random conveniently sampling among employees at private hospitals in Amman, Jordan through a structured self-administered survey questionnaire. In total, 457 usable responses were received and analysed using Smart PLS version 3.2.8 and SPSS version 23.0. The results of this study showed that dimensions of HRM practices (recruitment and selection, job design, training and development, employee empowerment and performance appraisal) have a significant positive influence on employees’ job satisfaction, except compensation. In turn, job satisfaction has significant influence on employee job performance. The dimensions of HRM practices comprises of recruitment and selection, job design, training and development and employee empowerment have significant influence on employee job performance through the mediating effect of job satisfaction. Job satisfaction does not mediate the relationship between performance appraisal and compensation and employee job performance. In addition, data analysis results also indicated that of P-O fit only moderates the relationship between training and development and employee job satisfaction. P-O fit does not moderate the relationship between recruitment and selection, job design, employee empowerment, performance appraisal and, compensation and between job satisfaction. From the academic perspective, this study highlights that level of fit between employees and their organization has significance influence on the relationship between HRM practices and job satisfaction. This in line with the idea propagated by social exchange theory on relation between the HRM and employee performance. From the practical aspect, this study has highlighted the important dimensions of HRM practice that the hospital management should focus in enhancing their employee performance, that indirectly will enhance its organisational performance and medical tourism industry in Jordan.